Design of multiple‐input multiple‐output transmit waveform and receive filter for extended target detection. Issue 9 (1st December 2015) - Karbasi, Seyyed Mohammad; Radmard, Mojtaba; Nayebi, Mohammad Mahdi; Bastani, Mohammad Hassan
Abstract : It is presumed that using multiple antennas at the transmit and receive sides can improve the radar's performance. One such improvement can be achieved in the detection of extended targets. However, in such multiple‐input multiple‐output systems, proper design of the transmit signals is an obstacle that can have significant influence on the performance. In this study, enforcing the peak‐to‐average‐ratio (PAR) constraint, the authors consider the problem of transmit space‐time code and receive space‐time filter design of such a system detecting extended targets. In addition, the power allocation among the different antennas is another degree of freedom that should be optimised under a total power constraint. Here, the authors derive a constrained optimisation procedure for transmit code, receive filter and transmit powers, which sequentially improves the signal‐to‐interference plus noise ratio of the system.